Engineers, society, and sustainability - Bell, Sarah (Sarah Jayne) (Synthesis lectures on engineering, technology, and society ;, 2011)
"Sustainable development is one of the key challenges of the twenty-first century. The engineering profession is central to achieving sustainable development. To date, engineering contributions to sustainability have focused on reducing the environmental impacts of development and improving the efficiency of resource use. This approach is consistent with dominant policy responses to environmental problems, which have been characterised as ecological modernisation. Ecological modernisation assumes that sustainability can be addressed by reforming modern society and developing environmental technologies. Environmental philosophers have questioned these assumptions and call into question the very nature of modern society as underlying the destruction of nature and the persistence of social inequality. Central to the crises of ecology and human development are patterns of domination and the separation of nature and culture."--Cover, p. [4].